FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN DETEKSI DINI PENYAKIT MENULAR SEKSUAL DI PUSKESMAS PANJANG KOTA BANDAR LAMPUNG - Satria Nandar Baharza; Mareza Yolanda Umar (JIKMI (Jurnal Ilmu Kesehatan Masyarakat Indonesia), 2020)
AbstractPuskesmas Panjang is one of the Puskesmas in Bandar Lampung with the highest number of STI cases compared to 28 Puskesmas in Bandar Lampung City. In the Mentari Clinic at the Panjang 5 Puskesmas in the last 5 months from November 2018 to March 2019, data were obtained of all patients who came for treatment and advanced screening of 354 people. 234 people or (66%) are female sex workers (FSW). The purpose of this study is to determine the factors associated with early detection of sexually transmitted diseases in the Panjang Bandar Lampung Health Center in 2019. This study uses a cross sectional study design. The population studied in this study were all EFAs with risk behavior in Panjang Bandar Lampung Health Center in 2019, totaling 647 people. Sample 125 people. Data collection using a questionnaire filled directly by respondents, univariate data analysis and bivariate analysis using the chi square test. The results showed the frequency distribution of respondents with low education of 57.5%, high knowledge of 51.2%, positive attitude of 55.2%, not doing early detection of sexually transmitted diseases 57.6%, There was a relationship of education, knowledge, attitude with early detection of disease sexually transmitted infections in Puskesmas Panjang Bandar Lampung in 2019. Suggestions for increasing WUS knowledge through providing health education about STDs and screening using more interesting media. Keywords : Factors, Early Detection, Sexually Transmitted Diseases